Characteristic analysis of a micro-/nanopositioning stage with coupling errors by the gravity. (August 2019) - Lin, Chao; Li, Pingyang; Shen, Zhonglei; Yu, Jiang
The piezo-actuated micro-/nanopositioning stages are often used in the current precision engineering applications, and the coupling deformation under the gravity of the stage is critical to error analysis. Considering the torsional deformation and bending deformation of the flexure hinges, the coupling error's analytical model of the positioning stage along the Z -axis is derived by using the virtual work principle and the elastic beam theory. The performance of the proposed theoretical model is analyzed and verified by the comparison between two common materials, and the quantities of the piezoelectric actuators are also analyzed with the impact on the coupling deformation of the stage along the Z -axis. Through the comparison and analysis of theoretical results, simulation results and experimental results, the maximum error between finite element analysis and experimental results is 11.43%, with the rest fluctuates within 10%, which proves the correctness of the theoretical model. It is concluded that gravity generated by the workload and the stage does have an influence on the coupling deformation along the Z -axis of the micro-/nanopositioning stage. It cannot be ignored in the analysis and consideration of the positioning stage.